Seasonal Variability of PM10 Chemical Composition Including 1,3,5-triphenylbenzene, Marker of Plastic Combustion and Toxicity in Wadowice, South Poland - Przemysław Furman; Katarzyna Styszko; Alicja Skiba; Damian Zięba; Mirosław Zimnoch; Magdalena Kistler; Anne Kasper-Giebl; Stefania Gilardoni (Aerosol and Air Quality Research)
Abstract The objective of this research was to evaluate the seasonal variation of the chemical composition of PM10 including polycyclic aromatic hydrocarbons (PAHs) and 1,3,5-triphenylbenzene (135TPB), which is a well known marker of plastic combustion. The presented work is a part of the project concerning assessment of air quality of small cities around Krakow agglomeration. Monitoring campaign was conducted between February and October 2017 in Wadowice, a small city in Krakow agglomeration, South Poland. To widen the knowledge of Krakow’s agglomeration air quality, other aerosol chemical components were analyzed. Ion chromatography (IC) was used for analysis of cations and anions, while gas chromatography-mass spectrometry (GC-MS) was used for PAHs. Samples were also analyzed for OC/EC (organic/elemental carbon) by thermal-optical analysis with a Sunset Laboratory carbon analyzer, Sunset Inc. The co-combustion of plastic in addition to conventional fuels and the respective impact on air quality is evaluated via the concentration of the marker compound 135TPB. Co-combustion of plastics with fuels resulted in a higher abundance of fluorene and most of 4–6 ring PAHs, in agreement with recent literature. Authors proved that other sources besides plastic burning, including road transport, residential heating, residential combustion, industrial emissions, affect the air quality in South Poland. The modeling tool Hybrid Single-Particle Lagrangian Integrated Trajectory model (HYSPLIT), developed by NOAA’s Air Resources Laboratory, was used to define the possible areas outside Wadowice contributing to urban air pollution.